A STUDY OF QUALITY INDICATORS FROM THE PERSPECTIVE OF HEADS OF SECONDARY SCHOOLS - Noorjehan Nazim Ganihar (Informascope, 2015)
A good quality education is one that enables all learners to realise the capabilities they   require to become economically productive, develop sustainable livelihoods, contribute to peaceful and democratic societies and enhance wellbeing. The learning outcomes that are required vary according to context but at the end of the basic education cycle must include threshold levels of literacy and numeracy and life skills including awareness and prevention of disease." (Tikly, 2010). Education quality programme encourages policy makers to take cognisance of changing national development needs, the kinds of schools that different learners attend and the forms of educational disadvantage faced by different groups of learners when considering policy options. A good quality education arises from interactions between three overlapping environments, namely the policy, the school and the home/ community environments. Creating enabling environments requires the right mix of inputs into each. the Education quality framework highlights the importance of accompanying processes within each environment that are key for ensuring that inputs get converted into desired outcomes. (Tikly, 2010). Creating a good quality education involves paying attention to the interface between each environment and ensuring that enabling inputs and processes have the effect of closing the gaps that often exist between them creating greater synergy and coherence.